Efeito da agitação ultrassônica na penetração intratubular e na resistência de união à dentina radicular de cimentos obturadores à base de silicato de cálcio - Carneiro, Verydianna Frota (2020)
The present study evaluated the effect of ultrasonic agitation on intratubular penetration and bond strength to root dentin provided by three calcium silicate-based endodontic obturator sealers, comparing them to AH Plus. Ninety-six disto-buccal canals in maxillary of human molars were prepared with Reciproc R50 files under irrigation with 2.5% NaOCl. They were then subjected to a final cleaning protocol with passive ultrasonic irrigation using NaOCl solutions at 2.5%, EDTA at 17% and NaOCl at 1.0%, sequentially, performing 3 cycles of 20 seconds in each one of them. Canals were then randomly divided into 8 experimental groups according to the sealer/treatment to be employed (n = 12): EndoSequence BC Sealer (ESBC), Sealer Plus BC (SPBC), Bio-C Sealer (BCS) and AH Plus (AH); with or without ultrasonic agitation (AUS). The filling of the canals was performed by the single cone technique with gutta-percha associated with the sealer that were manipulated as recommended by the manufacturers; Fluo-3 fluorophore was incorporated into the sealers (0.1% g/g) as a means of assessing penetration. After sealer insertion, in the groups submitted to AUS, it was used 2 cycles of 20 seconds at 30% power. After filling, the roots were kept in 37°C for 7 days. The specimens were sectioned transversely at 2, 4 and 6 mm from the anatomical apex; The sections were prepared and taken to the Laser Scanning Confocal Microscope to determine the depth of penetration into the dentinal tubules (mm). Subsequently, the specimens were submitted to the push-out test in a universal testing machine to evaluate the bond strength; the results obtained in Newtons were transformed into MPa and the type of failure determined in light microscopy with 40x magnification. The results of the penetration analysis showed that AUS did not significantly influence the intratubular penetration values. Considering into account the materials, significant differences were observed between ESBC compared to BCS and AH, all without AUS, at 2.0 mm from the root apex (p <0.05). In the push-out test, it was observed that AUS significantly increased the bond strength in the SPBC groups at 2.0 mm and BCS at 6.0 mm (p <0.05). When considering materials with the same treatment, significant differences were observed between groups AH and ESBC, both with and without AUS, at 2.0 mm (p <0.05). Depending on the results, under the conditions of the present study, it can be concluded that ultrasonic agitation did not influence intratubular penetration, but significantly increased the parameters of bond strength in the BCS groups, at the most cervical level, and SPBC, at the most apical level; also, that the tested bioceramic sealers showed a pattern of intratubular penetration and bond strength very similar to each other and with AH Plus.